A Takhrīj Study of The Hadith Al-Thaqalayn in Sunan Al-Tirmidhī - Maghza Rizaka; Muhammad Wahid Hasyim (Jurnal Indonesia Sosial Teknologi, 2024)
Al-Thaqalayn, an Islamic term denoting the Quran and the Ahl al-Bayt, is a fundamental resource for comprehending Islamic teachings and teachings. Extensive research has been devoted to Hadiths that pertain to al-Thaqalayn within the Islamic tradition. This article presents an analysis of the Hadith of al-Thaqalayn, focusing on examining and validating the Sanad and Matan traditions associated with al-Thaqalayn to determine their authenticity and reliability. The takhrij technique entails scrutinizing the text of Hadith al-Thaqalayn by focusing on the passages that are infrequently employed. The findings indicate that the Sanad (chain of narrators) of the Hadith of al-Thaqalayn is classified as Dha'īf (weak) due to the presence of narrators who engage in tables (concealing the identity of their sources) and others who have been deemed unreliable. Upon examining the content of the Hadith, it becomes evident that Hadith al-Thaqalayn is in harmony with the Quran, does not conflict with the more authoritative Hadith, is based on rational thinking, and possesses a framework that accurately conveys the teachings of the Prophet.